2021
DOI: 10.1111/jocn.15672
|View full text |Cite
|
Sign up to set email alerts
|

Impact of professional commitment on professional capability improvement and care quality dimensions: A multi‐wave study

Abstract: Aims and objectives: To examine how the three dimensions of professional commitment impact professional capabilities improvement and five key dimensions of care quality.Background: While professional commitment is known to retain nurses, we do not know how its three dimensions-affective, continuance and normative commitmentformulate five care quality dimensions: assurance, reliability, responsiveness, empathy and tangibles. Design:We used a three-wave, follow-up design to follow a sample of nurse participants.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Liking the nursing profession is an essential element of nursing profession commitment. This enables students to have a more stable and lasting psychological tendency to continue in the nursing profession, be more inclined to engage in spiritual care activities, and provide better healthcare (Chang et al, 2021 ). This result suggests that nursing schools should provide adequate information to help students understand the nursing profession in‐depth before choosing it as their major and improve their career interest.…”
Section: Disussionmentioning
confidence: 99%
“…Liking the nursing profession is an essential element of nursing profession commitment. This enables students to have a more stable and lasting psychological tendency to continue in the nursing profession, be more inclined to engage in spiritual care activities, and provide better healthcare (Chang et al, 2021 ). This result suggests that nursing schools should provide adequate information to help students understand the nursing profession in‐depth before choosing it as their major and improve their career interest.…”
Section: Disussionmentioning
confidence: 99%
“…Defined as a negative experience characterized by spending a lot of time and effort on work activities while neglecting other spheres of life, workaholism underlies the compulsion or uncontrollable urge to work which exudes a real obsession with work (Schaufeli et al, 2009). Nurses can experience high levels of workaholism as they have to deal with excessive job demands (Gillet et al, 2020a;Teng et al, 2010) and are highly committed to their profession (Chang et al, , 2021. Huyghebaert et al (2018a) also showed that workaholics experienced greater WFC.…”
Section: Background the Negative Outcomes Of Workaholism And Presenteeismmentioning
confidence: 99%
“…As can be seen in the NUMs' experiences, not only do they exhibit loyalty to the profession, but they attempt to inculcate that in their interactions with their team through role modeling and setting an example. This is encouraging as prior research found links between nurses' professional commitment and the motivation of teams (Galletta et al, 2019), an intention to improve and upgrade professional competence and capability (Chang et al, 2021), job satisfaction (Carcati et al, 2014), and patient care (Teng et al, 2019). The focus of the NUMs on the provision of quality healthcare and ensuring professional care of critical care patients is a central element of a relational type of psychological contract (Jones & Sambrook, 2010).…”
Section: Discussionmentioning
confidence: 77%